2021
DOI: 10.3389/fphar.2021.672054
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Naringin in Rheumatoid Arthritis: Network Pharmacology and Experimental Validation

Abstract: Rheumatoid arthritis is a chronic autoimmune disease characterized by persistent hyperplasia of the synovial membrane and progressive erosion of articular cartilage. Disequilibrium between the proliferation and death of RA fibroblast-like synoviocytes (RA-FLSs) is the critical factor in progression of RA. Naringin has been reported to exert anti-inflammatory and antioxidant effect in acute and chronic animal models of RA. However, the therapeutic effect and underlying mechanisms of naringin in human RA-FLS rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 51 publications
(52 reference statements)
1
51
0
Order By: Relevance
“…MAPK1, also known as ERK, regulates Bcl-2 expression and activates the caspase cascade. Several studies have revealed that the MAPK/ERK signaling pathway regulates cell differentiation and apoptosis and participates in the process of myocardial remodeling [ 55 ]. Wohlschlaeger et al confirmed that the levels of P-Akt and P-ERK in the myocardium of patients with HF increased.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK1, also known as ERK, regulates Bcl-2 expression and activates the caspase cascade. Several studies have revealed that the MAPK/ERK signaling pathway regulates cell differentiation and apoptosis and participates in the process of myocardial remodeling [ 55 ]. Wohlschlaeger et al confirmed that the levels of P-Akt and P-ERK in the myocardium of patients with HF increased.…”
Section: Discussionmentioning
confidence: 99%
“… 18 In the present study, the limma package of R was used to identify differentially expressed genes in RA synovial tissue and normal synovial tissue in GSE1919 and GSE77298 datasets. 19 Screening conditions were |log(FC)| ≥ 1 and adj. p val < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“… 26 Cytoscape visualizes PPI networks. 19 Molecular complex detection (MCODE), a plugin for Cytoscape, detects densely connected regions in large PPI networks representing molecular complexes. 27 The method employs vertex weighting based on local neighborhood densities, which allows for fine-tuning of clusters of interest without considering the rest of the network, and examines cluster interconnections associated with protein networks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations